The development of (ArtHis) interactive module in teaching and learning art history / Siti Zuraida Maaruf, Aliza Mohd Salleh and Noor Farhani Othman - Maaruf, Siti Zuraida; Mohd Salleh, Aliza; Othman, Noor Farhani (Research Management Centre (RMC), 2019)
The publishing material of art history pedagogy is known to have too many facts and students need to digest lots of information. The alternative methods of teaching and learning have become more reliable when technology-based methods have been found to be an effective pedagogical material. Thisstudy aims to design and develop an ArtHis Interactive Module for teaching and learning art history in Visual Art Education. For this reason, this study also investigates the impact of its usability in classroom and assesses the learning motivation of Visual Art students simultaneously. In this study, the Design and Developmental Research (DDR) method was used. Forthe most part, the ArtHisInteractive Module is developed by using ADDIE Model by considering the elements of design, technical, pedagogical, and the content which is appropriate to achieve the objectivesstated in Visual Art Education syllabus. Specifically, the development process was guided and supported by Dual Coding Theory and Flow Theory for information processing. For this purpose, the research focused on Form 5 Visual Artstudents. Microsoft PowerPoint was used to produce the interactive module with the aim of enhancing the students’ motivation in learning Art History. The finding showsthat the impact of learning art history usingArtHisInteractive Module has improved students’ conceptual understanding. It is also determined that 93.9 percent students agree that the exercises in the ArtHis Interactive Module help them to gauge their level of understanding and knowledge on the topics in Art History. In conclusion, ArtHis Interactive Module is used forthe purpose of improving teaching methods and increasing the motivation of students in Visual Art Education especially Art History topics